Age composition and prediction of optimum fishing mortality (Fmsy) for the Beluga, Stellate Sturgeon, Persian Sturgeon and Russian Sturgeon in the south part of the Caspian Sea - Taghavi, S.A. (2000)
Eight years (1990-1997) of the Beluga, Stellate Sturgeon, Persian Sturgeon and Russian Sturgeon in the south part of the Caspian Sea were analyzed for age composition. Yield-per-recruit curves were derived for each species based on growth parameters and mortality rates, and the optimum fishing mortality in terms of yield-per-recruit was calculated as a basis for sturgeon fishery management in the Caspian Sea. The results of eight years catches from this part of the Caspian Sea show that the age structure of all species has changed and a trend to become younger for fish of both sexes is apparent. On the other hand, fishing composition, is confined to some special age groups. Inspection of yield-per-recruit model confirms the overfishing of the sturgeons in the Caspian Sea and suggested that the fishing mortality showed be reduced by decreasing fishing effort. It seems that the population of the Beluga, probably because of the higher quality of its caviar, are more depleted, therefore in order to maintain the spawning stock, the harvesting of Beluga showed be much restricted for several years. Published